Organizational Health in Amando Cope College: A Basis for Developing Strategic Plan - Engay, Federico B. (International Journal of Research in Interdisciplinary Studies, 2025)
Work is an important activity in one’s life. It provides individuals with improved chances of experiencing health, financial, and social advantages in life. The objective of the study is to determine the organizational health of the institution, whether it is balanced with the stakeholders’ expectation or whether it should improve its current practices and policies that would affect the employees’ morale and productivity. It was found out that majority of the employees in Amando Cope College have 1-5 years of experience in their respective field of specialization, likewise, most of the respondents were engaged in teaching professions, along soft or hard skills, it was also found out that teaching and mentoring were the most relevant to their position. On the other hand, board passer, educationally prepared and experiential readiness were found to be the respondents’ achievements under career profile. On professional goal; enhance expertise in one’s field, earn a higher salary, grow professional network, and obtain higher credentials were found to be their career objectives in joining the organization. The two groups of respondents rated the following: leadership, employees, workplace, and success shows that the healthy career trajectory are always manifested. The two groups of respondents rated the indicators along employees engagement; work with co-workers in the attainment of organization’s goals and accountabilities are made clear to everyone in one’s team, understand changes in the organization, and engaged happily in one’s work were found to be engaged in full extent. In the light of the foregoing findings and conclusions, the following recommendations are offered: The organization’s management should provide its personnel with trainings, seminars, activities, and appraisal program to further enhance their skills and capabilities; Administrators may be encouraged to revisit organizational practices that characterize the organization; the institution may implement new strategies to uplift the employees’ morale and well-being like recognition, rewards, incentives and appreciation; and the Office of the President may be furnished with the strategic plan offered by different department head using the researcher’s formatted template.